Enhanced performance of metal-semiconductor-metal UV photodetectors on Algan/Gan Hemt structure via periodic nanohole patterning - Razeen, Ahmed S. (2024)
AlGaN/GaN High Electron Mobility Transistor (HEMT) structures offer superior electrical and material properties that make them ideal for the fabrication of high-performance Ultraviolet photodetectors (UV PDs), especially using the metal-semiconductor-metal (MSM) configuration. However, the metal layout of the MSM design and crystal defects in multi-stack HEMTs can reduce photocurrent and degrade device performance. Nano-structuring of the AlGaN/GaN surface with different nanofeatures is a promising approach to improve light absorption efficiency and increase device response. In this work, AlGaN/GaN HEMT MSM UV photodetectors with enhanced performance parameters by engineering the surface with periodic nanohole arrays are demonstrated. Optical simulations are used to optimize the design of the nanoholes' periodicity and depth. Unpatterned and nanohole-patterned devices with varying nanohole depths are fabricated, and their performance shows substantial enhancement with the incorporation of nanoholes. The device with 40 nm deep nanoholes and 230 nm array periodicity shows the highest performance in terms of photocurrent (0.15 mA), responsivity (1.4 × 105 A W−1), UV/visible rejection ratio (≈103), and specific detectivity (4.9 × 1014 Jones). These findings present a HEMT-compatible strategy to enhance UV photodetector performance for power optoelectronic applications, highlighting that nanohole patterning is a promising prospect for advancements in UV photodetection technology.